Association of rs1544410 and rs7975232 Polymorphisms and Serum Vitamin D Levels with Psoriasis Susceptibility and Severity: A Case–Control Study in Egyptian Patients - Mohamed AA; Elhussain E; Fawzy N; Sakr Y; Salah El-dien M; Abbas AM; Hussein MS; Nassar N; Ezzat O; El-Amir RY; Ibrahim S; Bedair NI (Dove Medical Press, 2022)
Amal Ahmed Mohamed,1 Eman Elhussain,2 Naglaa Fawzy,3 Yasser Sakr,3 Marwa Salah El-dien,4 Abbas Mohammed Abbas,5 Maha S Hussein,6 Nourelhuda Nassar,7 Omnia Ezzat,8 Reham Yousry El-Amir,9 Sarah Ibrahim,10 Nermeen Ibrahim Bedair11,12 1Department of Biochemistry and Molecular Biology, National Hepatology and Tropical Medicine Research institute, Cairo, Egypt; 2Department of Clinical and Chemical Pathology, Faculty of Medicine, Cairo University, Giza, Egypt; 3Department of Clinical Pathology, National Institute of Diabetics and Endocrinology, Cairo, Egypt; 4Department of Community, Environmental and Occupational Medicine, Faculty of Medicine, Benha university, Banha, Egypt; 5Department of Biochemistry, Faculty of Medicine, Cairo University, Giza, Egypt; 6Department of Dermatology and Andrology, Medical Research and Clinical Studies Institute, National Research Center, Cairo, Egypt; 7Department of Clinical Pathology, Elsahel Teaching Hospital, Cairo, Egypt; 8Department of Biochemistry, Faculty of Pharmacy, Egyptian Russian University, Cairo, Egypt; 9Department of Public Health, Faculty of Medicine, Cairo University, Giza, Egypt; 10Department of Dermatology, Faculty of Medicine, Cairo university, Cairo, Egypt; 11Department of Dermatology, Andrology, Sexual Medicine and STDs, Faculty of Medicine, Helwan University, Cairo, Egypt; 12Department of Dermatology and Andrology, Armed Forces College of medicine, Cairo, EgyptCorrespondence: Nermeen Ibrahim Bedair, Department of Dermatology, Andrology, Sexual Medicine and STDs, Faculty of Medicine, Helwan University, Cairo, Egypt, Email nermeen.bedair@med.helwan.edu.egBackground: Vitamin D is a regulatory factor for skin immune functions through vitamin D receptor, which is expressed on many immune cells. Vitamin D receptor is located on chromosome 12q 13.11 and has many single nucleotide polymorphisms. Some of them were hypothesized to be associated with psoriasis. Psoriasis is a genetic disease that is greatly affected by environmental factors.Methods: A total of 135 psoriasis patients and 114 healthy controls were recruited. Both had a measurement of serum vitamin D and two vitamin D receptor variants:, rs1544410: G > A (HGVS:NC_000012.12:g.47846052) and rs7975232: C > A (HGVS: NC_000012.12:g.47845054). We assessed the relationship between vitamin deficiency as well as the two gene polymorphisms with psoriasis susceptibility and severity.Results: Serum vitamin D levels were not significantly different between cases and controls. However, a significant association between vitamin D levels and severity was observed. We attributed this to our finding that rs7975232 was more significantly polymorphic among cases than controls, while rs1544410 polymorphism did not show a significant difference among the 2 groups.Conclusion: We did not find a significant difference in serum vitamin D levels between cases and controls. Yet, psoriasis severity was significantly associated with serum vitamin D levels. We attributed this to other findings that the vitamin D receptor rs7975232 gene is polymorphic in psoriasis patients. At the same time, rs1544410 was not significantly more polymorphic in psoriasis patients. Both genes' polymorphisms were associated with severe psoriasis.Keywords: vitamin D deficiency, vitamin D receptors polymorphisms, single nucleotide polymorphism, ApaI, BsmI, rs7975232, rs1544410, psoriasis